2015
DOI: 10.1021/acs.jpcc.5b03727
|View full text |Cite
|
Sign up to set email alerts
|

Crystal-Domain Orientation and Boundary in Highly Ordered Organic Semiconductor Thin Film

Abstract: Conduction of electric charges is often done in polycrystalline materials. Unavoidably, the crystallite size, orientation and domain boundaries (DBs) affect the transport of the charge carriers. It is particularly so for organic semiconductors known to be highly anisotropic and strongly dependent on DBs. Understanding those effects will have a strong impact on improving the performance of organic electronic and optoelectronic devices. Herein, we report our investigation on the crystal-domain orientation and bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…4b), with mobility values ranging over two orders of magnitude, from 2.4 × 10 −5 to 4.4 × 10 −3  cm 2  V −1  s −1 . A similar relationship has been reported between the charge-carrier mobility and (crystal) grain sizes for OFETs based on pentacene52, copper phthalocyanine,53 oligo(thiophene)s54 and P3HT crystals55. In all of these previously reported cases, the increase in mobility was attributed to a decreased density of grain boundaries.…”
Section: Resultssupporting
confidence: 81%
“…4b), with mobility values ranging over two orders of magnitude, from 2.4 × 10 −5 to 4.4 × 10 −3  cm 2  V −1  s −1 . A similar relationship has been reported between the charge-carrier mobility and (crystal) grain sizes for OFETs based on pentacene52, copper phthalocyanine,53 oligo(thiophene)s54 and P3HT crystals55. In all of these previously reported cases, the increase in mobility was attributed to a decreased density of grain boundaries.…”
Section: Resultssupporting
confidence: 81%
“…The mobility of CuPc/p-6P thin films have been reported that a hole field-effect mobility as high as 0.18 cm 2 V −1 s −1 could be obtained, which was about 2 orders of magnitude higher than that of CuPcbased field-effect transistors (FETs) (≈2.1 × 10 −3 cm 2 V −1 s −1 ). [19,20] The results in Figure 2b,c show that, under the dark condition, the off-current of CuPc/p-6P and CuPc phototransistors is about 1.6 × 10 −11 and 5.2 × 10 −11 A, respectively, while the on-current of two devices is about 1.4 × 10 −5 and 2.3 × 10 −6 A, respectively. Because the highly ordered CuPc thin films with large-size grain can greatly improve the charge transport, and the electrical properties of CuPc/p-6P phototransistors are much better than that of CuPc FETs.…”
Section: Resultsmentioning
confidence: 95%
“…[17,18] Based on disordered CuPc and highly ordered CuPc/p-6P thin films, the corresponding phototransistors were fabricated, and the structure schematic of CuPc/p-6P heterojunction photo transistors is shown in Figure 2a. [19,20] The results in Figure 2b,c show that, under the dark condition, the off-current of CuPc/p-6P and CuPc phototransistors is about 1.6 × 10 −11 and 5.2 × 10 −11 A, respectively, while the on-current of two devices is about 1.4 × 10 −5 and 2.3 × 10 −6 A, respectively. The mobility of CuPc/p-6P thin films have been reported that a hole field-effect mobility as high as 0.18 cm 2 V −1 s −1 could be obtained, which was about 2 orders of magnitude higher than that of CuPcbased field-effect transistors (FETs) (≈2.1 × 10 −3 cm 2 V −1 s −1 ).…”
Section: Resultsmentioning
confidence: 97%
“…1c ). The strong dependence of µ on the density of grain boundaries is expected and has been experimentally verified multiple times, This is typically explained by the presence of shallow or deep valleys trapping charge carriers at the grain boundary 40 , 44 , 46 48 .…”
Section: Introductionmentioning
confidence: 75%
“…In practice, this means that if the grain boundary density is high, all free charge can be trapped at the grain boundary leading to a depletion of the grain itself 15 , 46 . Finally, in the literature it is typically assumed, that the main mechanism that limits µ upon transport through a grain boundary are energy barriers due to trapped majority carriers 14 , 15 , 45 , 46 , 48 . Again, up to now no attention has been paid to the role of energy barriers at grain boundaries that do not originate from filled valleys, even though one could imagine them to have a dramatic impact on charge transport in the case that they are located at a grain boundary that percolates across the entire channel.…”
Section: Introductionmentioning
confidence: 99%